MEDICAL-PEDAGOGICAL CONTROL OF PHYSIOLOGICAL INDICATORS DURING CLASSES IN VARIOUS TYPES OF PHYSICAL ACTIVITY (Physical Culture and Sport: Scientific Perspective, 2025)
The article explores the theoretical and practical foundations of medical-pedagogical control of physiological indicators during various types of physical activity classes. The primary focus is on defining the role of control as a structured system that ensures the alignment of pedagogical influences, the functional state of the body, and the achieved results with the planned goals of physical education. The main types of control are described: preliminary, operational, and current, along with their tasks and implementation features at different stages of the educational and training process. The concepts of pedagogical control and self-control are discussed separately, emphasizing their significance in forming individual physical education programs and ensuring class safety.An analysis of modern approaches to organizing medical-pedagogical control is presented, based on the principles of comprehensiveness, systematicity, and objectivity. The main methods for assessing the functional state of the cardiovascular, respiratory, nervous, and endocrine systems are described, including the use of pulseometry, spirometry, functional tests, and integrated digital monitoring systems. The importance of comprehensive testing for obtaining an integral assessment of the psychophysiological state of individuals engaged in physical activity and determining the effectiveness of pedagogical influence is highlighted.Particular attention is given to organizing control for individuals with special medical needs, emphasizing the necessity of adapting standard methods to individual capabilities and health status. The role of injury prevention, sanitary-hygienic control, and sanitary-educational work in ensuring a safe educational environment is outlined. The article concludes by emphasizing the importance of implementing modern monitoring technologies and an interdisciplinary approach to enhance the effectiveness of physical education and maintain health.
Keywords: medical-pedagogical control; physiological indicators; physical activity; physical education